A Review on Transformer Design Optimization Using Artificial Intelligence Technique: Developing AI-Based Software for Optimizing Transformer Design (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of transformer design is to achieve the dimensions with all sections of the transformer in such a way that it is commercially viable, has good efficiency , at same time, can gratify all the restrictions placed by international requirements user specifications. With the advent of Artificial Intelligence (AI) techniques, it is now probable to reduce active part cost, manufacturing cost, and total owning cost, while simultaneously satisfying international standards and constraints. In Indian industries, AI techniques are yet to be employed for TDO problems. The objectives of the paper to develop software based on AI techniques that could be utilized for the optimal design of distribution transformer.